The Influence of Tax Avoidance, Managerial Ownership and Profitability on Tax Payment Levels - Sari, Dela Puspita; Dewi, Anita Kusuma; Damayanti, Damayanti (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This study aims to analyze the effects of tax avoidance, managerial ownership, and profitability on the level of tax payments in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Methodology/approach: This study uses secondary data from financial reports. A purposive sampling method was applied, resulting in 85 observations. Data were processed using SPSS version 25 and multiple linear regression analysis. The research includes classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). Results/findings: The results show that tax avoidance has a positive and significant effect on tax payments, managerial ownership has no significant effect, and profitability has a positive but insignificant effect. Simultaneously, the three variables significantly influenced tax payments, with results shaped by the COVID-19 pandemic and related tax policies. Conclusions: This study concludes that tax avoidance is the dominant factor affecting corporate tax payments, whereas managerial ownership and profitability do not have significant effects. However, all three variables jointly affect the tax payment levels. Limitations: This research is limited to property and real estate companies listed on the IDX during 2019–2023, therefore, the findings may not be generalizable to other sectors or periods. Contributions: This study contributes to the accounting and taxation literature in Indonesia and provides insights for policymakers, tax authorities, and company management.